Experimental and Theoretical Study of the Effect of Adding Ion Exchange Bed to RO Desalination System - A. Kabeel; A. Khalil; Y. EL-Samadony; Maisa Sharaf (Journal of Engineering Research - Egypt)
In the present work, a novel hybrid reverse osmosis (RO) system with ion exchange (IX) bed is designed and studied experimentally and theoretically. This is done by adding a new IX bed before conventional RO system. Natural zeolite is chosen as a cheap adsorbent for IX process. The present work investigates IX process in continuous water flow bed. The effect of natural zeolite mass, water flow rate, bed diameter and natural zeolite grain size on the performance of IX bed is studied. Moreover, water recovery, permeate water and membrane flux of RO system are studied and compared with the conventional RO system. The results showed that the proposed system water recovery, permeate water and membrane flux is higher than that for conventional RO system by 9% to 27.1%, 8.5% to 29 % and 30% respectively at different inlet water concentrations for zeolite bed with 250 g weight. Finally, a good agreement between theoretical and experimental results is performed.